The Role of IL-23 in the Development of Th17 Lymphocytes in Pulmonary Tuberculosis Patients - T. E. Kononova; O. I. Urazova; V. A. Serebryakova; S. P. Chumakova; O. A. Vasilyeva; A. E. Sanina (Туберкулез и болезни лёгких)
The objective: to evaluate the role of IL-23 in the development of Th17 lymphocytes in patients with different clinical and pathogenetic forms of pulmonary tuberculosis.Subjects and Methods. 165 pulmonary tuberculosis patients were examined. Venous blood was used for tests. Mononuclear leukocytes were isolated by centrifugation and monocytes were extracted and transformed into dendritic cells. The concentration of IL-23 in the supernatants of culture suspensions of dendritic cells was determined by ELISA. Immunophenotyping of Th17 lymphocytes (CD4+CD161+IL-17A+ cells) was performed by flow cytometry. Real-time PCR was used to determine the expression of the RORC2 transcription factor gene in lymphocytes.Results. In patients with infiltrative drug susceptible and drug resistant pulmonary tuberculosis against the background of normal production of IL-23 by dendritic cells, an increase in blood level of Th17 lymphocytes and the level of mRNA of the RORC2 transcription factor gene was registered. The course of disseminated pulmonary tuberculosis (regardless of drug susceptibility and resistance) is associated with pronounced decrease in the concentration of IL-23 in vitro and the absence of response from Th17 lymphocytes.